Climate Change and Migration : Evidence from the Middle East and North Africa - Wodon, Quentin; Liverani, Andrea; Joseph, George; Bougnoux, Nathalie (Washington, DC: World Bank, 2014)
Climate change is a major source of concern in the Middle East and North Africa (MENA) region, and migration is often understood as one of several strategies used by households to respond to changes in climate and environmental conditions, including extreme weather events. This study focuses on the link between climate change and migration. Most micro-level studies measure climate change either by the incidences of extreme weather events or by variation in temperature or rainfall. A few studies have found that formal and informal institutions as well as policies also affect migration. Institutions that make government more responsive to households (for example through public spending) discourage both international and domestic migration in the aftermath of extreme weather events. Migration is often an option of last resort after vulnerable rural populations attempting to cope with new and challenging circumstances have exhausted other options such as eating less, selling assets, or removing children from school. This study is based in large part on new data collected in 2011 in Algeria, Egypt, Morocco, Syria, and the Republic of Yemen. The surveys were administered by in-country partners to a randomly selected set of 800 households per country. It is also important to emphasize that neither the household survey results nor the findings from the qualitative focus groups are meant to be representative of the five countries in which the work was carried, since only a few areas were surveyed in each country. This report is organized as follows: section one gives synthesis. Section two discusses household perceptions about climate change and extreme weather events. Section three focuses on migration as a coping mechanisms and income diversification strategy. Section four examines other coping and adaptation strategies. Section five discusses perceptions about government and community programs.